Engineering perpendicular magnetic anisotropy in Fe via interstitial nitrogenation: N choose K - Hongbin Zhang; Imants Dirba; Tim Helbig; Lambert Alff; Oliver Gutfleisch (APL Materials, 2016)
In this work, combining experimental results and first principles calculations, we show that interstitial nitrogen not only serves for inducing tetragonality in α′-Fe8Nx but is also essential for achieving a high degree of perpendicular magneto-crystalline anisotropy, K. Our results demonstrate that the orbital magnetic moments of the iron atoms above and below N in the direction of magnetization are much more susceptible to the applied magnetic field than their in-plane counterparts, leading to a giant value of K as compared to a hypothetical distorted material without N.